Evidence of strategic information uncertainty around opportunistic insider purchases - Rahman, Dewan; Oliver, Barry; Faff, Robert (Journal of Banking & Finance, 2020)
We investigate whether CEOs strategically increase information uncertainty surrounding their insider stock purchases. We find that in the month before and during CEO stock purchases, information uncertainty in their news releases increases, which correlates with lower stock prices. This finding is not evident in the month after insider purchases and thus suggests CEOs’ strategic behavior. Our key findings of strategic information uncertainty are confirmed using multi-faceted fixed effects regressions, a quasi-natural experimental design, and numerous other robustness checks.